Analytical, Classical Mechanical and Semi Empirical Study of Transition Metal Complexes of (2E,2’E)-2,2’-(5,5-Dimethylcyclohexane- 1,3-diylidene)dihydrazine Carboxamide - A. Jaleel, U.C; Rakhila, M.; Parameswaran, Geetha (Asian Journal of Chemistry, 2010)
Six new transition metal complexes of (2E,2'E)-2,2'-(5,5-dimethylcyclohexane- 1,3-diylidene)dihydrazine carboxamide (dimedone bis semicarbazone = H2DSC) have been synthesized. These complexes were characterized mainly by elemental analysis, molar conductance and magnetic susceptibility measurements, electronic and infrared spectral studies. The results obtained were analytically correlated with molecular mechanical and semi empirical calculations.